Telehealth: Alternative Self-Management Promotion in People with Diabetes During Covid Pandemic - Mangklakeeree, Nutcharat; Mangklakeree, Terachai (Journal of The Royal Thai Army Nurses, 2023)
The epidemic of coronavirus disease 2019 (Covid-19) over the past 2 years has affected the way of life, economy, and society widely. Including health care service system that has changed form of health care service. Information communication technology has been applied in diabetes care during pandemic. This article aimed to provide the evidence of telehealth which focus on modalities and usage of telehealth for delivery healthcare service during covid 19 crisis, the outcomes and the challenging of applying telehealth for self-management in diabetes people. The usage of telehealth enables the provision of synchronous (real-time) and asynchronous (store and forward) consultation and monitoring between patients and clinicians. The advantages of telehealth application to diabetes management enhanced health behaviors for glycemic control during the pandemic and remote health care. The barriers of telehealth were human resource, budget, equipment, and time, including the diabetes patient. However, there are still challenges for applying telehealth in diabetes management after pandemic.